Strategi Pengembangan Usaha Industri Rumah Tangga Tempe di Desa Sendang Mulya Sari Kabupaten Konawe : (Studi Kasus Usaha Tempe Bu Ratmi) - Sinta Dewi; Sara Evi Rahayu (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The purpose of this study was to analyze internal and external strategies in the development of the tempeh industry in Sendang Mulya Sari Village, Tonggauna District, Konawe Regency. The determination of the research sample was carried out intentionally (purposive sampling) using key informants, in this study the key informant was Mrs. Ratmi, the owner of the tempeh business. This study is a qualitative descriptive study using analysis tools, namely SWOT. The development strategy of the